THE PATHOPHYSIOLOGY OF ULCERATIVE COLITIS. THE CURRENT STATE OF THE PROBLEM OF ETIOLOGY, EARLY DIAGNOSIS AND TREATMENT - Bakhodirovna, Salimova Nigora (PT ANTIS International Publisher, 2024)
General Background: Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory bowel diseases that significantly impact patients' quality of life and present substantial healthcare challenges globally. Specific Background: This review provides a comprehensive analysis of contemporary literature regarding the etiology, pathophysiology, diagnosis, and treatment of UC and CD. It highlights the prevalence of these conditions both worldwide and specifically in Uzbekistan, emphasizing their clinical significance. Knowledge Gap: Despite advancements in understanding these diseases, challenges persist in the early diagnosis and management of UC and CD, particularly due to the absence of standardized diagnostic tests for assessing intestinal inflammation. Aims: The objective of this review is to synthesize current knowledge on the interplay between UC and primary sclerosing cholangitis, explore therapeutic options available internationally, and identify effective pharmacological agents used to achieve and maintain remission. Results: The findings reveal critical insights into the epidemiological trends of UC and CD, the complex relationship between these diseases and primary sclerosing cholangitis, and the varied therapeutic strategies employed in different countries. Novelty: This review uniquely addresses the underexplored relationship between UC and primary sclerosing cholangitis while providing a focused discussion on therapeutic modalities that may enhance patient outcomes. Implications: The insights gained from this analysis underscore the need for improved diagnostic methods and tailored treatment approaches to better manage UC and CD, ultimately informing clinical practice and guiding future research in this area.